P-wave terminal force in lead V1 is associated with recurrence after catheter ablation in patients with paroxysmal atrial fibrillation and normal left atrial size - Wang, Zhao; Wang, Binhao; Yang, Yiheng; Yang, Xiaolei; Che, Ying; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2024)
Background A previous investigation reported that an abnormal P-wave terminal force in lead V1 (PTFV1) is a marker for electrical remodeling of the left atrium (LA). We aimed to assess the relationship of PTFV1 with LA tachyarrhythmia (LATA) recurrence after radiofrequency catheter ablation (RFCA) in patients with paroxysmal atrial fibrillation (PAF) and normal LA size. Methods Patients with PAF and normal LA size (LA volume index < 34 ml/m2) who underwent RFCA were consecutively included between January 2018 and December 2020 and divided into two groups based on the presence (recurrence group) or absence (nonrecurrence group) of LATA recurrence. PTFV1 was measured according to preprocedural electrocardiography. The association between PTFV1 and the recurrence of LATA was investigated. Results A total of 385 patients were included. After a median follow-up period of 745 (467, 977) days, 109 (28.3%) patients experienced LATA recurrence. PTFV1 was greater in the recurrence group. Multivariate Cox regression analysis demonstrated that the hazard ratio and 95% confidence interval for PTFV1 per 1,000 μV*ms increase and PTFV1 > 4,000 μV*ms were 1.22 (1.13–1.32, p < 0.001) and 2.32 (1.54–3.48, p < 0.001), respectively. Conclusion PTFV1 is an independent predictor for LATA recurrence after RFCA in patients with PAF and normal LA size.